Constitutional Legal Framework of Local Government in Russia and South Africa - R. Aliev (BRICS Law Journal, 2021)
The article examines certain issues relating to the constitutional and legal regulation of local self-government in Russia and South Africa in the context of their cooperation within the partnership of the BRICS countries, as well as the constitutional reforms of local self-government carried out in these states. It is noted that, despite the fundamental difference in the historical prerequisites for their implementation, the constitutional and legal approaches to determining the legal nature of local self-government and identifying its status in the general system of public authority in these countries have similar features. This circumstance, according to the author, indicates the potential for a convergence of the systems of legal regulation of these countries and actualizes the need to exchange experience in legal regulation in this area in order to solve similar problems of development of local self-government.